NO Initial ITS Start location: l4 0: l0 -> l1 : x^0'=x^post0, y^0'=y^post0, (y^0-y^post0 == 0 /\ x^0-x^post0 == 0 /\ 1+x^0 <= 0), cost: 1 1: l0 -> l2 : x^0'=x^post1, y^0'=y^post1, (-y^post1+y^0 == 0 /\ -x^0+x^post1+y^0 == 0 /\ -x^0 <= 0), cost: 1 2: l2 -> l0 : x^0'=x^post2, y^0'=y^post2, (-y^post2+y^0 == 0 /\ x^0-x^post2 == 0), cost: 1 3: l3 -> l0 : x^0'=x^post3, y^0'=y^post3, (1+x^0+y^0 <= 0 /\ x^0-x^post3 == 0 /\ 1-x^0 <= 0 /\ y^0-y^post3 == 0), cost: 1 4: l4 -> l3 : x^0'=x^post4, y^0'=y^post4, (x^0-x^post4 == 0 /\ -y^post4+y^0 == 0), cost: 1 Removed unreachable rules and leafs Start location: l4 1: l0 -> l2 : x^0'=x^post1, y^0'=y^post1, (-y^post1+y^0 == 0 /\ -x^0+x^post1+y^0 == 0 /\ -x^0 <= 0), cost: 1 2: l2 -> l0 : x^0'=x^post2, y^0'=y^post2, (-y^post2+y^0 == 0 /\ x^0-x^post2 == 0), cost: 1 3: l3 -> l0 : x^0'=x^post3, y^0'=y^post3, (1+x^0+y^0 <= 0 /\ x^0-x^post3 == 0 /\ 1-x^0 <= 0 /\ y^0-y^post3 == 0), cost: 1 4: l4 -> l3 : x^0'=x^post4, y^0'=y^post4, (x^0-x^post4 == 0 /\ -y^post4+y^0 == 0), cost: 1 Applied preprocessing Original rule: l0 -> l2 : x^0'=x^post1, y^0'=y^post1, (-y^post1+y^0 == 0 /\ -x^0+x^post1+y^0 == 0 /\ -x^0 <= 0), cost: 1 New rule: l0 -> l2 : x^0'=x^0-y^0, x^0 >= 0, cost: 1 Applied preprocessing Original rule: l2 -> l0 : x^0'=x^post2, y^0'=y^post2, (-y^post2+y^0 == 0 /\ x^0-x^post2 == 0), cost: 1 New rule: l2 -> l0 : TRUE, cost: 1 Applied preprocessing Original rule: l3 -> l0 : x^0'=x^post3, y^0'=y^post3, (1+x^0+y^0 <= 0 /\ x^0-x^post3 == 0 /\ 1-x^0 <= 0 /\ y^0-y^post3 == 0), cost: 1 New rule: l3 -> l0 : (1+x^0+y^0 <= 0 /\ -1+x^0 >= 0), cost: 1 Applied preprocessing Original rule: l4 -> l3 : x^0'=x^post4, y^0'=y^post4, (x^0-x^post4 == 0 /\ -y^post4+y^0 == 0), cost: 1 New rule: l4 -> l3 : TRUE, cost: 1 Simplified rules Start location: l4 5: l0 -> l2 : x^0'=x^0-y^0, x^0 >= 0, cost: 1 6: l2 -> l0 : TRUE, cost: 1 7: l3 -> l0 : (1+x^0+y^0 <= 0 /\ -1+x^0 >= 0), cost: 1 8: l4 -> l3 : TRUE, cost: 1 Eliminating location l3 by chaining: Applied chaining First rule: l4 -> l3 : TRUE, cost: 1 Second rule: l3 -> l0 : (1+x^0+y^0 <= 0 /\ -1+x^0 >= 0), cost: 1 New rule: l4 -> l0 : (1+x^0+y^0 <= 0 /\ -1+x^0 >= 0), cost: 2 Applied deletion Removed the following rules: 7 8 Eliminating location l2 by chaining: Applied chaining First rule: l0 -> l2 : x^0'=x^0-y^0, x^0 >= 0, cost: 1 Second rule: l2 -> l0 : TRUE, cost: 1 New rule: l0 -> l0 : x^0'=x^0-y^0, x^0 >= 0, cost: 2 Applied deletion Removed the following rules: 5 6 Eliminated locations on linear paths Start location: l4 10: l0 -> l0 : x^0'=x^0-y^0, x^0 >= 0, cost: 2 9: l4 -> l0 : (1+x^0+y^0 <= 0 /\ -1+x^0 >= 0), cost: 2 Applied acceleration Original rule: l0 -> l0 : x^0'=x^0-y^0, x^0 >= 0, cost: 2 New rule: l0 -> l0 : x^0'=x^0-n0*y^0, (x^0 >= 0 /\ n0 >= 0 /\ x^0-y^0*(-1+n0) >= 0), cost: 2*n0 Applied recurrent set Original rule: l0 -> l0 : x^0'=x^0-y^0, x^0 >= 0, cost: 2 New rule: l0 -> [5] : (x^0 >= 0 /\ 1+y^0 <= 0), cost: NONTERM Applied fixed-point processor Original rule: l0 -> l0 : x^0'=x^0-y^0, x^0 >= 0, cost: 2 New rule: l0 -> [5] : (x^0 >= 0 /\ y^0 == 0), cost: NONTERM Applied deletion Removed the following rules: 10 Accelerated simple loops Start location: l4 11: l0 -> l0 : x^0'=x^0-n0*y^0, (x^0 >= 0 /\ n0 >= 0 /\ x^0-y^0*(-1+n0) >= 0), cost: 2*n0 12: l0 -> [5] : (x^0 >= 0 /\ 1+y^0 <= 0), cost: NONTERM 13: l0 -> [5] : (x^0 >= 0 /\ y^0 == 0), cost: NONTERM 9: l4 -> l0 : (1+x^0+y^0 <= 0 /\ -1+x^0 >= 0), cost: 2 Applied chaining First rule: l4 -> l0 : (1+x^0+y^0 <= 0 /\ -1+x^0 >= 0), cost: 2 Second rule: l0 -> l0 : x^0'=x^0-n0*y^0, (x^0 >= 0 /\ n0 >= 0 /\ x^0-y^0*(-1+n0) >= 0), cost: 2*n0 New rule: l4 -> l0 : x^0'=x^0-n0*y^0, (1+x^0+y^0 <= 0 /\ -1+x^0 >= 0 /\ x^0-y^0*(-1+n0) >= 0), cost: 2+2*n0 Applied chaining First rule: l4 -> l0 : (1+x^0+y^0 <= 0 /\ -1+x^0 >= 0), cost: 2 Second rule: l0 -> [5] : (x^0 >= 0 /\ 1+y^0 <= 0), cost: NONTERM New rule: l4 -> [5] : (1+x^0+y^0 <= 0 /\ -1+x^0 >= 0), cost: NONTERM Applied deletion Removed the following rules: 11 12 13 Chained accelerated rules with incoming rules Start location: l4 9: l4 -> l0 : (1+x^0+y^0 <= 0 /\ -1+x^0 >= 0), cost: 2 14: l4 -> l0 : x^0'=x^0-n0*y^0, (1+x^0+y^0 <= 0 /\ -1+x^0 >= 0 /\ x^0-y^0*(-1+n0) >= 0), cost: 2+2*n0 15: l4 -> [5] : (1+x^0+y^0 <= 0 /\ -1+x^0 >= 0), cost: NONTERM Removed unreachable locations and irrelevant leafs Start location: l4 15: l4 -> [5] : (1+x^0+y^0 <= 0 /\ -1+x^0 >= 0), cost: NONTERM Computing asymptotic complexity Proved nontermination of rule 15 via SMT. Proved the following lower bound Complexity: Nonterm Cpx degree: Nonterm Solved cost: NONTERM Rule cost: NONTERM Rule guard: (1+x^0+y^0 <= 0 /\ -1+x^0 >= 0)